Impact of extracts from Heamatococcus pluvialis and Magnolia officinalis, as well as vitamin E supplementation, on a number of blood biochemical indicators in laying hens - Husam H Nafea,; Mohanad Th Ahmed, (International Journal of Medical Toxicology and Legal Medicine, 2024)
The experiment aimed to study the Individual and combining effect of adding Heamatococcus pluvialis extract and Magnolia officinalis extract compared to vitamin E to the diet on some serum biochemical parameters of laying hens in the late phase of the laying cycle and under conditions of heat stress. At 52 weeks of age, 120 Lohman Brown laying hens were used, and the experiment continued for five periods (28 days period-1) 20 weeks, from 20/3/2022 to 7/8/2022, The laying hens were randomly distributed into eight treatments, with 5 replications for one treatment and 3 hens for one replicate, The treatments included: T1 standard diet without any additives, T2 adding vitamin E to the diet at a level of 300 mg kg-1 feed, T3 and T4 adding Heamatococcus pluvialis extract to the diet at levels of 200 and 400 mg kg-1 feed respectively T5 and T6 adding Magnolia officinalis extract to the diet at the level of 200 and 400 mg kg-1 feed respectively and T7 and T8 adding Heamatococcus pluvialis extract mixture at a level of 100 mg kg-1 feed and Magnolia officinalis extract at a level of 100 mg kg-1 feed and 200 mg kg-1 feed and Magnolia officinalis extract at a level of 200 mg kg-1 feed respectively to the diet. The results showed that the addition of natural antioxidants (Heamatococcus pluvialis extract and Magnolia officinalis extract) and synthetic (vitamin E) to the diet of laying hens led to a significant improvement (P≤ 0.05) in all biochemical parameters in blood serum compared to treatment T1, and it was noted that treatment T8 (a mixture of Heamatococcus pluvialis extract and Magnolia officinalis extract) had a significant superiority (P≤ 0.05) in the level of total protein and globulin, and a significant decrease (P≤ 0.05) in the level of cholesterol, triglycerides and LDL in the blood serum of chickens. We conclude from this that adding natural antioxidants to the diet of aged laying hens which was cultured during the hot season in Iraq leads to an improvement in the blood serum's biochemical characteristics and decreases the effect of oxidative stress.